A New Framework for Enhancing (Academic) Integrity - MacLeod, Paul (Canadian Perspectives on Academic Integrity, 2021)
Why is academic integrity so important? This might seem like a frivolous question, but it really is not. Academic integrity is crucial if we consider that one of the prime missions of higher education is to help form the intellectual and moral outlook of the future leaders of our society. By so doing, higher education can contribute to societies whose members abide by the rule of law and maintain, for the most part, adherence to a shared legal and moral code. Maintaining the ethical standards of the academy is also crucial to maintaining public trust in our educational institutions but this imperative pales in importance to education’s role in helping to form ethical citizens. Without a shared ethical base, societies can easily slide into rampant corruption and chaos. While there has been significant work done on theoretical frameworks for promoting ethics in higher education, the vast majority of research on academic integrity actually focuses on student motivation to commit academic misconduct and how instructors and institutions can control, or limit this behavior. Current research indicates that this focus on student behavior has not worked. This presentation will present a framework for operationalizing integrity for life on a systems level with research-based guidelines for enhancing individual, institutional, education system and, ultimately, societal integrity while contributing to the development of a more holistic view of academic ethics that will be applicable to the Canadian context and beyond. Participants will take away insights to creating a roadmap to academic integrity in their own institutions and communities. Keywords: Academic integrity; ethics, framework, academic dishonesty, Canada